2020
DOI: 10.1038/s42003-020-0942-0
|View full text |Cite|
|
Sign up to set email alerts
|

Methylation deficiency disrupts biological rhythms from bacteria to humans

Abstract: The methyl cycle is a universal metabolic pathway providing methyl groups for the methylation of nuclei acids and proteins, regulating all aspects of cellular physiology. We have previously shown that methyl cycle inhibition in mammals strongly affects circadian rhythms. Since the methyl cycle and circadian clocks have evolved early during evolution and operate in organisms across the tree of life, we sought to determine whether the link between the two is also conserved. Here, we show that methyl cycle inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…In the seagrass Posidonia oceanica , such physiological rhythms have been correlated with the expression patterns of related genes (e.g., photosynthesis and respiratory genes), which seem to be responsible for driving such changes throughout the day [ 54 ]. However, their upstream regulatory mechanisms, which could involve epigenetic and/or epitranscriptomic mechanisms [ 39 , 40 , 41 , 42 ], remain unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the seagrass Posidonia oceanica , such physiological rhythms have been correlated with the expression patterns of related genes (e.g., photosynthesis and respiratory genes), which seem to be responsible for driving such changes throughout the day [ 54 ]. However, their upstream regulatory mechanisms, which could involve epigenetic and/or epitranscriptomic mechanisms [ 39 , 40 , 41 , 42 ], remain unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that epigenetic and epitranscriptomic regulations affect the expression of clock components in several organisms [ 28 , 40 , 41 ], but only few studies have been conducted on the epigenetic and post-transcriptional controls of circadian clock functions in plants [ 42 , 43 , 44 , 45 ] and almost none on the role of RNA methylation (m 6 A) in regulating clock-related genes [ 46 , 47 ]. In mammals, it has been demonstrated that a large number of transcripts encoding core clock components, as well as clock output genes, are enriched in m 6 A methylation sites [ 40 , 48 ] and that changes in their m 6 A levels can affect circadian rhythms, cellular growth, and ultimately survival [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mouse embryonic fibroblasts, this m6A reduction upon AHCY inhibition is functionally linked to a delay in processing RNAs from circadian rhythm genes, thus impacting their oscillatory behavior response (Fustin et al, 2013). Extending this observation, Fustin et al (2020) have recently found that targeting AHCY activity with 3-deazaneplanocin A (DZnep) produces a loss in the oscillatory transcriptional response of circadian-associated genes in different organisms (from unicellular algae to humans). The loss of the oscillatory transcriptional activation of the Hes7 gene during somitogenesis on DZnep-treated mouse embryos suggests that methylation flux, directed by AHCY, is a universal regulator of biological circadian rhythms in metazoans (Fustin et al, 2020).…”
Section: Molecular Effects On Dna Rna and Histone Methylationmentioning
confidence: 92%
“…To reduce sample complexity, we employed the uniquely minimal cellular and genomic complexity of the model cell Ostreococcus tauri , a picoeukaryotic alga. This cell type is well established as a cellular model for circadian rhythms across eukaryotes 6, 9, 19 , and is highly amenable to culture under natural diurnal versus constant circadian conditions. Our results provide a rare insight into the complex relationship between environmental and circadian regulation of protein abundance across time, revealing a strikingly differential spatiotemporal proteome under these two conditions.…”
Section: Introductionmentioning
confidence: 99%